Pelatihan Kader Dokter Gigi Kecil Tentang Karies Gigi di Sekolah Dasar Negeri Kota Palembang - Deynilisa, Saluna; Hanum, Nur Adiba; Ismalayani, Ismalayani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2019)
Dental and oral health is an important thing, so dental and oral health care efforts need to be fostered from an early age. The target or target of health education and health services aimed at a certain age group or population greatly determines the success of a health program. Therefore, the target of health education and health services aimed at school-age childrenSmall dentist cadres are students who meet the criteria and are trained to participate in carrying out some efforts to maintain and improve health for themselves, friends, family and the environment whose quality is continuously improved in order to achieve a goal, namely improving the quality of dental and oral health. The thing that underlies the importance of small dentist training activities is the school age community (6-18 years old) which makes up a large part of the Indonesian population (+ 29%), it is estimated that 50% of this number are school children, children in the middle ages. growth and development so that it is still easy to be fostered and guided (Entjang, 2000). The methods implemented are the formation of cadres, dental and oral health counseling, training and mentoring. The number of cadres in the SD is 12 students consisting of grades 3, 4 and 5. The extension methods used are lectures, demonstrations. The tools used are dental models, posters, props The expected results of this service are: 1) Increased knowledge of small dentist cadres about dental and oral caries and the skills of small dentists in carrying out simple dental examinations. 2) Increased knowledge, attitudes, actions of elementary school students so that they can support public health. 3) The product is